2017
DOI: 10.1016/j.jiph.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and antibiotic susceptibility of pathogens isolated from adults with hospital-acquired and ventilator-associated pneumonia in intensive care unit

Abstract: Hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) are the most common hospital infections with the highest prevalence in intensive care units (ICU). The aim of this study was to investigate prevalence of bacterial pathogens isolated from ICU patients with HAP/VAP and reveal their susceptibility rates in order to establish a basis for empirical antibiotic therapy. Prospective cohort study was conducted in central ICU of Clinical Centre Kragujevac, Serbia, from January 2009 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 22 publications
7
21
0
3
Order By: Relevance
“…This observation might indicate that males are more susceptible to VAP acquisition than females. Other studies showed also the majority of males among VAP-suspected patients [13,17,18,19]. In this study, the reason for admission of the majority of VAP cases was medical problems like other previous studies [4,20].…”
Section: Discussionsupporting
confidence: 77%
“…This observation might indicate that males are more susceptible to VAP acquisition than females. Other studies showed also the majority of males among VAP-suspected patients [13,17,18,19]. In this study, the reason for admission of the majority of VAP cases was medical problems like other previous studies [4,20].…”
Section: Discussionsupporting
confidence: 77%
“…However, a recent small retrospective study by FENG et al [50] of the microbial aetiology of HAP and VAP reported that the leading pathogens were similar in both entities, with a predominance of Acinetobacter baumannii and P. aeruginosa in VAP, and Klebsiella pneumoniae and S. aureus in HAP. Moreover, the authors demonstrated an increase in the MDR bacteria in VAP, with a lower susceptibility of P. aeruginosa in VAP compared to HAP, as reported in previous studies [51,52]. The results of FENG et al [50] are in line with those of a less recent prospective observational study by ESPERATTI et al [13] about ICU-acquired nosocomial pneumonia, where the proportion of relevant pathogens in patients with an isolated organism was similar, suggesting that the cause and the outcome depend on the underlying conditions of the patients rather than previous intubation.…”
Section: Aetiology and Treatmentsupporting
confidence: 81%
“…The antimicrobial resistance patterns and the percentage of MDR strains observed reiterates the concerning results from other Serbian studies [12,22]. Overall resistance rates of 88% for cephalosporins, 85% and 75% for gentamycin and amikacin, 92% for ciprofloxacin, and 56% for carbapenems are higher compared to most European countries [19].…”
Section: Discussionsupporting
confidence: 80%